Compassionate Conservation is indistinguishable from traditional forms of conservation in practice - Bobier, Christopher A.; Allen, Benjamin L. (Frontiers in Psychology, 2022)
Animal welfare and ethics are important factors influencing wildlife conservation practice, and critics are increasingly challenging the underlying ethics and motivations supporting common conservation practices. “Compassionate Conservationists” argue that all conservationists should respect the rights of individual sentient animals and approach conservation problems from a position of compassion, and that doing so requires implementing practices that avoid direct harm to individual animals. In this way Compassionate Conservationists seek to contrast themselves with “Traditional Conservationists” who often express consequentialist decision-making processes that ostensibly aim to dispassionately minimize net animal harms, resulting in the common use of practices that directly harm or kill some animals. Conservationists and other observers might therefore conclude that the two sides of this debate are distinct and/or that their policy proscriptions produce different welfare outcomes for animals. To explore the validity of this conclusion we review the ethical philosophies underpinning two types of Compassionate Conservation—deontology and virtue ethics. Deontology focusses on animal rights or the moral duties or obligations of conservationists, whereas virtue ethics focusses on acting in ways that are virtuous or compassionate. We demonstrate that both types permit the intentional harm and killing of animals when faced with common conservation problems where animals will be harmed no matter what the conservationist does or does not do. We then describe the applied decision-making processes exhibited by Compassionate Conservationists (of both types) and Traditional Conservationists to show that they may each lead to the implementation of similar conservation practices (including lethal control) and produce similar outcomes for animals, despite the perceived differences in their ethical motivations. The widespread presence of wildlife conservation problems that cannot be resolved without causing at least some harm to some animals means that conservationists of all persuasions must routinely make trade-offs between the welfare of some animals over others. Compassionate Conservationists do this from an explicit position of animal rights and/or compassion, whereas Traditional Conservationists respect animal rights and exhibit this same compassion implicitly. These observations lead to the conclusion that Compassionate Conservation is indistinguishable from traditional forms of conservation in practice, and that the apparent disagreement among conservationists primarily concerns the effectiveness of various wildlife management practices at minimizing animal harm, and not the underlying ethics, motivations or morality of those practices.